An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Visualization of meteorological data using an interactive flight - Koenig, M; Lenz, Christian; Domik, Gitta (Proceedings. Computer Graphics International (Cat. No. 98EX149))

Fuzzy dynamics of compartmental systems - Hüllermeier, Eyke (in Proceedings EUFIT-98 6th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Efficient Consistency Checking for Embedded Memories - N. Yarmolik, Vyacheslav; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Efficient Consistency Checking for Embedded Memories - N. Yarmolik, Vyacheslav; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

A Distributed Computer Architecture for Fast Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold

An optimal checkpointing interval for real-time systems - Karl, Holger; Werner, Matthias (Proc. Intl. Conf. Parallel and Distributed Processing Techniques and Applications)

Snarks and reducibility - Brinkmann, Gunnar; Steffen, Eckhard (Ars Combinatoria)

Chromatic-index-critical graphs of Orders 11 and 12 - Brinkmann, Gunnar; Steffen, Eckhard (European J. Combinatorics)

Classification and characterizations of snarkse - Steffen, Eckhard (Discrete Mathematics)

Acceleration of satisfiability algorithms by reconfigurable hardware - Platzner, Marco; De Micheli, Giovanni (Proceedings of the 8th International Workshop on Field Programmable Logic and Applications (FPL))

Reflectance Anisotropy of GaAs(100): Theory and Experiment - Shkrebtii, A. I.; Esser, N.; Richter, W.; Schmidt, Wolf Gero; Bechstedt, F.; Fimland, B. O.; Kley, A.; Del Sole, R. (Physical Review Letters)

Geometry and electronic structure of InP(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Atomic structure of InP(001)-(2×4): A dimer reconstruction - Schmidt, Wolf Gero; Bechstedt, F.; Esser, N.; Pristovsek, M.; Schultz, Ch.; Richter, W. (Physical Review B)

In-induced (4 × 2) reconstructions of GaAs(001) surfaces - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Applied Surface Science)

Ultrasonic sensors for process monitoring and chemical analysis state of the art and trends - Hauptmann, Peter; Lucklum, Ralf; Püttmer, Alf; Henning, Bernd (Sensors and Actuators A: Physical)

Zum Partikeltransport in Elektrischen Abscheidern - Schmid, Hans-Joachim

Knowledge based controller selection for electrical drives with imperfect mechanic - Schutte, F.; Beineke, S.; Grotstollen, H. (IECON '98. Proceedings of the 24th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.98CH36200))

Modellierungund Regelung stromrichtergespeister Ultraschall-Wanderwellenmotoren - Maas, J.

Axiomatische Ethik - Peckhaus, Volker (Zwischen Kant und Hare. Eine Evaluation der Ethik Leonard Nelsons)
Autoreferat: Zbl. Math. 914.00010.

Identification of nonlinear two-mass systems for self-commissioning speed control of electrical drives - Beinke, S.; Wertz, H.; Schutte, F.; Grotstollen, H.; Fröhleke, N. (IECON '98. Proceedings of the 24th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.98CH36200))

A high efficiency single-phase power factor corrected switched mode rectifier - Wallmeier, P.; Richter, J.; Fröhleke, N.; Grotstollen, H.; Langemeyer, L.; Margaritis, B. (IECON '98. Proceedings of the 24th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.98CH36200))

Improved analytical modeling of conductive losses in gapped high-frequency inductors - Wallmeier, P.; Fröhleke, N.; Grotstollen, H. (Conference Record of 1998 IEEE Industry Applications Conference. Thirty-Third IAS Annual Meeting (Cat. No.98CH36242))

Automated optimization of high frequency inductors - Wallmeier, P.; Fröhleke, N.; Grotstollen, H. (IECON '98. Proceedings of the 24th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.98CH36200))

Zermelo, Ernst (1871–1953) - Peckhaus, Volker (Routledge Encyclopedia of Philosophy, Bd. 9: Sociology of knowledge to Zoroastrianism)

Gentzen, Gerhard Karl Erich (1909–45) - Peckhaus, Volker (Routledge Encyclopedia of Philosophy, Bd. 4: Genealogy to Iqbal)

Mixed-Mode BIST Using Embedded Processors - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Hertwig, Andre (Mixed-Mode BIST Using Embedded Processors)

Mixed-Mode BIST Using Embedded Processors - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Hertwig, Andre (Journal of Electronic Testing Theory and Applications - JETTA)

“Russell’s Paradox”, Rezension von Alejandro R. Garciadiego. Bertrand Russell and the Origins of the Set-theoretic ‘Paradoxes’. Basel, Boston and Berlin: Birkhäuser Verlag, 1992. Spanish edition: Bertrand Russell y los origines de las “paradojas” de la theoría de conjuntos. Madrid: Alianza Editorial, 1992 - Peckhaus, Volker (Russell)

Helena M. Pycior, Symbols, Impossible Numbers, and Geometric Entanglement. British Algebra through the Commentaries on Newton’s Universal Arithmetic. Cambridge University Press, Cambridge 1997 - Peckhaus, Volker (Erkenntnis)

The Heuristic Function of the Axiomatic Method [Abstract] - Peckhaus, Volker (Twentieth World Congress of Philosophy. Abstracts of Invited and Contributed Papers)

Ocular toxicity from ethambutol: a review of four cases and recommended precautions. - Sivakumaran, P; Harrison, AC; Marschner, J; Martin, P (N Z Med J)

Ocular toxicity from ethambutol: a review of four cases and recommended precautions. - Sivakumaran, P; Harrison, AC; Marschner, J; Martin, P (N Z Med J)

Ewald, William (Hg.), "From Kant to Hilbert. A Source Book in the Foundations of Mathematics, 2 Bde"., The Clarendon Press: Oxford/Oxford University Press: New York 1996 - Peckhaus, Volker (Mathematical Reviews)

Spectra and total energies from self-consistent many-body perturbation theory - Schindlmayr, Arno; Pollehn, Thomas Joachim; Godby, Rex William (Physical Review B)
With the aim of identifying universal trends, we compare fully self-consistent electronic spectra and total energies obtained from the GW approximation with those from an extended GWΓ scheme that includes a nontrivial vertex function and the fundamentally distinct Bethe-Goldstone approach based on the T matrix. The self-consistent Green’s function G, as derived from Dyson’s equation, is used not only in the self-energy but also to construct the screened interaction W for a model system. For all approximations we observe a similar deterioration of the spectrum, which is not removed by vertex corrections. In particular, satellite peaks are systematically broadened and move closer to the chemical potential. The corresponding total energies are universally raised, independent of the system parameters. Our results, therefore, suggest that any improvement in total energy due to self-consistency, such as for the electron gas in the GW approximation, may be fortuitous.

Systematic vertex corrections through iterative solution of Hedin's equations beyond the GW approximation - Schindlmayr, Arno; Godby, Rex William (Physical Review Letters)
We present a general procedure for obtaining progressively more accurate functional expressions for the electron self-energy by iterative solution of Hedin's coupled equations. The iterative process starting from Hartree theory, which gives rise to the GW approximation, is continued further, and an explicit formula for the vertex function from the second full cycle is given. Calculated excitation energies for a Hubbard Hamiltonian demonstrate the convergence of the iterative process and provide further strong justification for the GW approximation.

Assessment of the GW approximation using Hubbard chains - Pollehn, Thomas Joachim; Schindlmayr, Arno; Godby, Rex William (Journal of Physics: Condensed Matter)
We investigate the performance of the GW approximation by comparison to exact results for small model systems. The role of the chemical potentials in Dyson's equation as well as the consequences of numerical resonance broadening are examined, and we show how a proper treatment can improve computational implementations of many-body perturbation theory in general. Exchange-only and GW calculations are performed over a wide range of fractional band fillings and correlation strengths. We thus identify the physical situations where these schemes are applicable.

Klassische philosophische Texte von Frauen. 2nd ed

„Das Ausmaß der Trauer“ – Negativdarstellung und Engagement bei Max Frisch - Block, Iris (Literatur in Wissenschaft und Unterricht)

Die inhaltliche Dynamik des wirklichen Lebens bei Max Frisch. Zum Wandel eines Sujetbegriffs - Block, Iris (StudiaNeophilologica)

Visuelle Spezifikations- und Modellierungstechniken - Müller, Wolfgang; Sturm, Jörgen (it - Information Technology)

Wissen und Handeln: Ein Lehrbuch zur Geschichte der Ethik für den Gymnasialunterricht unter Berücksichtigung der Schriften von Philosophinnen

[Rez. v.] Francis Haskell. Die Geschichte und ihre Bilder. Die Kunst und die Deutung der Vergangenheit. Aus dem Englischen übersetzt von Michael Bischoff. Verlag C.H. Beck, München 1995 - Süßmann, Johannes (Archiv für Sozialgeschichte)

Dummett, Michael, “Introductory Remarks”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 69–76 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Spalt, Detlef D., „Exaktheit als Konstante, Begriffe im Wandel des mathematischen Denkens. Zur Analysis im 19. und 20. Jahrhundert“, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 45–59 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Murawski, Roman, “On the Philosophical Meaning of Reverse Mathematics”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 173–184 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cellucci, Carlo, “From Closed to Open Systems”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 206–220 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Maddy, Penelope, “Wittgenstein’s Anti-Philosophy of Mathematics”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 52–72 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wang, Hao, “What is Logic?”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 11–23 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Brosch, Anette, “TLP 4.0312”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 167–172 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)